PENILAIAN FASILITAS JALUR PEDESTRIAN DARI ASPEK SAFETY, HEALTH, AND ENVIRONMENT (SHE) - Dinda Fardila; Henricus Priyosulistyo; Andreas Triwiyono (Inersia : Jurnal Teknik Sipil dan Arsitektur, 2018)
ABSTRACTPedestrian way is a space providing services for pedestrian in carrying out their activities. This research aims to evaluate the liability of the pedestrian facilities in complying the prevailing standards and safety, health, and environment (SHE) instead of determining the priority rank for improving the performance of pedestrian facilities. This research was conducted on the pedestrian way of Malioboro area in Yogyakarta, by field survey on 23-27 January 2018. The research used questionnaires with incidental sampling technique. The data was performed and statistically analyzed by SPSS program in terms of Importance Performance Analysis (IPA) method and inference analysis using Rank Spearman's truth test. The result of this research showed that the pedestrian way had generally met the standards (57.14%) but several facilities (38.10%) did not meet the criteria and 4.76% was not available in the pedestrian way of Malioboro.The level of performance of pedestrian facilities based on SHE was mostly high (satisfied). The facilities that must be improved were the cleanliness of the pedestrian way and the toilet. Some respondences were still able to accept the conditions as follow: the speed of motor bike, the noises, street vendor layout, shop sign layout and the quality of building materials. Keywords: Environment, Importance Performance Analysis (IPA), Pedestrian way, Safety, Health ABSTRAKJalur pedestrian merupakan ruang yang memberikan layanan kepada pejalan kaki dalam melakukan aktivitasnya. Kajian ini bertujuan untuk mengevaluasi kelayakan kondisi fasilitas jalur pedestrian terhadap standar yang berlaku, safety, health, and environment (SHE), dan menentukan prioritas layanan yang diperlukan untuk peningkatan kinerja fasilitas jalur pedestrian. Kajian ini dilakukan pada jalur pedestrian Kawasan Malioboro dengan cara survey lapangan pada tanggal 23-27 Januari 2018. Kajian ini menggunakan kuesioner berskala Likert dengan teknik pengambilan sampel insidental sampling.Analisis data menggunakan analisis statistik deskriptif, metode Importance Performance Analysis (IPA) dan analisis inferensi (uji korelasi  Spearman Rank). Hasil kajian menunjukkan bahwa fasilitas jalur pedestrian telah memenuhi standarsebesar 57,14%, tetapi 38,10% tidak memenuhi kriteria dan 4,76% fasilitas tidak terdapat di jalur pedestrian kawasan Malioboro. Fasilitas yang harus ditingkatkan kinerjanya pada prioritas utama adalah tingkat kebersihan pedestrian dan toilet. Beberapa pedestrian masih dapat menerima kondisi berikut :kecepatan pengendara bermotor, kebisingan, tata letak PKL, tata letak papan nama toko dan kualitas bahan bangunan. Kata kunci: Environment, Importance Performance Analysis (IPA), Jalur pedestrian, Safety, Health